The social stratification of the Madurese society and its implications on the usage of Bhasa Madhura - Lukman Fajariyah (SIMULACRA: JURNAL SOSIOLOGI, 2020)
This paper explored the life of social stratification of the Madurese society and the usage of Bhasa Madhura (Madurese language) by using two theories, namely Talcott Parsons’ structural functionalism theory and stratification theory by Paul B. Horton. The research method used in this research was a qualitative descriptive method. The authors based this research on literature review and empirical data by observation and interviews. Through data analysis, the author uncovered several findings. First, the social stratification styles of the Madurese society in the context of status, class, and occupation was divided into three types, namely the levels of the oreng kenek, pongghaba, and parjaji communities. Second, the social stratification styles from religious context were divided into six types, including keyae, ajji, modin, bindharah, santre, and banne santre. Third, the usage of Bhasa Madhura in the Madurese social stratification was divided into different honorifics, from the highest and most polite honorific to the lowest or impolite honorific. Besides that, the usage of abhasa (enggi bunten) styles and ta’abhasa (enja’-iye) styles also occur in some aspects of Madurese conditional and contextual life. The findings of this study could be used to advise the preservation of Bhasa Madhura in the social stratification realm.